Systems of Hamilton-Jacobi equations. Issue 4 (2nd October 2019) - Cambronero, Julio; Álvarez, Javier Pérez
Abstract : In this article we develop a generalization of the Hamilton-Jacobi theory, by considering in the cotangent bundle an involutive system of dynamical equations.